An exploratory study of small-scale farmers’ perceptions of land degradation in Komatipoort and how it influences their livelihoods - Lombard, A. (Antoinette) (University of Pretoria, 2023)
Mini Dissertation (MSW (Social Work))--University of Pretoria, 2023.